SATISFACTION ON COMPENSATION AFFECTING MOTIVATION OF STAFF AT KHUAN KROD SUBDISTRICT ADMINISTRATIVE ORGANIZATION, THUNG SONG, NAKHON SI THAMMARAT - Thinphabat, Jaru; Khaoklom, Uangfa; Laemuso, Nureeta; Kawsongmuang, Chawiwan (Journal of MCU Nakhondhat, 2023)
The objectives of this research were to 1) explore staffs’ satisfaction on compensation at Khuan Krod Subdistrict Administrative Organization. 2) investigate staffs’ motivation at Khuan Krod Subdistrict Administrative Organization and 3) examine the satisfaction on compensation that affects the motivation of staff at Khuan Krod Subdistrict Administrative Organization, Thung Song, Nakhon Si Thammarat. This is a quantitative research. The population of the study were 40 staff working at Khuan Krod Subdistrict Administrative Organization in Thung Song, Nakhon Si Thammarat and 37 of them were selected as the samples by using accidental sampling technique. Questionnaire was used as a research instrument. The statistics used to analyze the data were frequency, mean, standard deviation and Pearson Product Moment Correlation Coefficient. The results revealed that 1) the overall satisfaction of staff working at Khuan Krod Subdistrict Administrative Organization was at the highest level; social leader social award, indirect monetary compensation, career reward and direct monetary compensation respectively. 2) the overall motivation of staff working at Khuan Krod Subdistrict Administrative Organization was at a high level in all aspects. Hygiene factor was at the highest level. Motivation factor came at the second stage. When considering each aspect, policy and organization management were the highest level while interpersonal relation subordinates and command appeared the second stage. And 3) the satisfaction on compensation that affects the motivation of staff at Khuan Krod Subdistrict Administrative Organization was positively related at a high level significantly different at the statistical level of .01.